Toll‐like receptors: Role in inflammation and therapeutic potential. (21st December 2013) - Kay, Emma; Scotland, Ramona S.; Whiteford, James R.
Abstract Inflammation is an essential process in response to injury and infection. However, under certain circumstances dis‐regulation of this process can lead to pathologies such as rheumatoid arthritis, atherosclerosis, lupus, and is a contributory factor in the progression of many cancers. The Toll‐like family of receptors (TLRs) has major roles in the initiation of the inflammatory response and as such has attracted much focus for their potential as therapeutic targets. Here we review the role of TLRs in the inflammatory response and associated disease and examine how this important family of molecules might be targeted for therapeutic benefit. © 2013 BioFactors, 40(3):284–294, 2014